2020
DOI: 10.1038/s41598-020-75998-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of feline teeth highlights the role of matrix metalloproteinase 9 (MMP9) in tooth resorption

Abstract: Tooth resorption (TR) in domestic cats is a common and painful disease characterised by the loss of mineralised tissues from the tooth. Due to its progressive nature and unclear aetiology the only treatment currently available is to extract affected teeth. To gain insight into TR pathogenesis, we characterised the transcriptomic changes involved in feline TR by sequencing RNA extracted from 14 teeth (7 with and 7 without signs of resorption) collected from 11 cats. A paired comparison of teeth from the same ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are a family of 23 structurally related proteolytic enzymes, which can degrade almost all components of the extracellular matrix [ 87 ]. MMP-9 promotes bone resorption by degrading extracellular matrix macromolecules around and on the surface of bone trabeculae and mediates osteoclast adhesion and migration to resorption sites [ 88 ]. MMP-13, which breaks down proteoglycans in the extracellular matrix, such as proteoglycans and collagen, is thought to be the main protease responsible for cartilage destruction in rheumatoid arthritis [ 78 ].…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are a family of 23 structurally related proteolytic enzymes, which can degrade almost all components of the extracellular matrix [ 87 ]. MMP-9 promotes bone resorption by degrading extracellular matrix macromolecules around and on the surface of bone trabeculae and mediates osteoclast adhesion and migration to resorption sites [ 88 ]. MMP-13, which breaks down proteoglycans in the extracellular matrix, such as proteoglycans and collagen, is thought to be the main protease responsible for cartilage destruction in rheumatoid arthritis [ 78 ].…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…Not all functional teeth are shed at the same time (Grieco and Richman 2018) so we expected approximately every other tooth to be invaded by odontoclasts. Indeed using the TRAP stain (Tartrate resistant acid phosphatase is coded by the ACP5 gene) a marker for odontoclasts (Fuenzalida et al 1999; Lee et al 2020; Sahara et al 1996; Takada et al 2004), showed many TRAP+ cells inside the pulp cavities of resorbing teeth (Fig. 3B,B’; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tooth resorption is a common nosological entity in domestic cats and presents itself as a defect in hard tissues (enamel, dentin, and cementum), due to the progressive loss of calcified dental tissue by the action of odontoclasts [ 12 ]. The main physiological role of odontoclasts is to promote root resorption of deciduous teeth and the hard tissues surrounding their roots, allowing the occurrence of tooth eruption of permanent teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The main physiological role of odontoclasts is to promote root resorption of deciduous teeth and the hard tissues surrounding their roots, allowing the occurrence of tooth eruption of permanent teeth. In adult cats, these cells, due to still unknown causes, become deregulated and destroy dental tissues [ 12 ]. Several etiological factors have been suggested as the cause of this disease, such as chronic oral inflammation (periodontal disease and feline chronic gingivostomatitis; infectious diseases, namely those caused by the feline immunodeficiency virus (FIV) and the feline leukemia virus (FeLV) [ 13 ]; hypervitaminosis D with changes in calcium metabolism [ 14 ], mechanical trauma [ 15 ], or the breed of the animal, although none of these factors has been confirmed as the direct cause of resorption [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation